Living standards, poverty and inequality in the UK: 2019 - Pascale Bourquin; Jonathan Cribb; Tom Waters; Xiaowei Xu (Institute for Fiscal Studies (IFS), 2019)
This report examines how living standards - most commonly measured by households' incomes - have changed for different groups in the UK, and the consequences that these changes have for income inequality and for measures of deprivation and poverty. In this latest report, we focus in particular on those people who are poorest in society, with two of our three main chapters focusing on poverty.
Keywords: 330